1975
DOI: 10.1185/03007997509114794
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-intestinal absorption and transplacental transfer of amoxycillin during labour and the influence of metoclopramide

Abstract: The absorption of amoxycillin from the gastro-intestinal tract, with or without oral metoclopramide, has been evaluated. Levels of amoxycillin in the maternal blood and liquor prior to the induction of labour were of a therapeutic level against many organisms. However, absorption during labour, as reflected by maternal blood levels at delivery and cord blood levels, suggests that amoxycillin is poorly absorbed and may not reach adequate therapeutic levels in the fetus. Oral metoclopramide did not improve the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…Intramuscular metocJopramide (lOmg im) had no effect on the narcotic-induced delay in emptying rate. Amoxycillin absorption is also delayed and therapeutic plasma or amniotic fluid concentrations are not achieved during labour (Buckingham et al, 1975). Absorption was not improved by metoclopramide but no information was given about the administration of analgesics to the patients in this study.…”
Section: Gastric Emptying and Drug Absorptioncontrasting
confidence: 48%
“…Intramuscular metocJopramide (lOmg im) had no effect on the narcotic-induced delay in emptying rate. Amoxycillin absorption is also delayed and therapeutic plasma or amniotic fluid concentrations are not achieved during labour (Buckingham et al, 1975). Absorption was not improved by metoclopramide but no information was given about the administration of analgesics to the patients in this study.…”
Section: Gastric Emptying and Drug Absorptioncontrasting
confidence: 48%
“…One study reported amoxicillin serum concentrations during pregnancy 19 . This study offered limited data in that it examined amoxicillin pharmacokinetics only at the time of delivery, did not have a control group, and used a microbiologic assay for the measurement of serum amoxicillin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Oral absorption is unreliable during labor and does not improve with the concurrent intramuscular injection of metoclopramide (BUCKINGHAM et al 1975). Placental transfer appears to be slow, although concentrations in cord blood and amniotic fluid eventually surpass those in maternal serum (BERGOGNE-BEREZIN et al 1979 b).…”
Section: Amoxicillinmentioning
confidence: 96%